(untitled) (Challenges of the Future, 2025)
Research Questions (RQs): 1. What are the key challenges that media production students face in balancing study, work, and personal commitments? 2. What is the overall impact of the use of artificial intelligence (in all segments of activity – school, work, leisure) on the organisation of the lives of media production students? Purpose: The purpose of the research is to analyse the organisation of students’ lives and propose strategies and tools to reduce negative stress and improve the balance between studies, work, and free time. Method: The research is based on monitoring the preparation and implementation of the project "Improving the organisation of your life", which was carried out over three years by more than 80 FUDŠ students in the course Management and Organisation of Media Production. We used the methods of survey, project analysis and discussions. Artificial intelligence (ChatGPT) is involved in all phases of the research and project. Results: Most students (over 70%) are not satisfied with the organisation of their lives before the start of the project and 70% of them report stress. The situation has improved greatly with the project "Improving the organisation of your life". Basic theoretical insights, techniques such as Time Blocking and Pomodoro, the Eisenhower Matrix method, the use of digital tools (Trello, Notion, Google Calendar) and especially ChatGPT improved productivity and reduced the feeling of being overwhelmed. The results show the positive impact of physical exercise and relaxation techniques on managing stress. Organization: The research offers practical solutions, such as the integration of time management techniques and digital tools that can improve the study programme and the performance of students and the organisations in which they participate. Artificial intelligence programmes offer important opportunities, but we must take care to ensure that rationalisation studies are not engaged in at the expense of the quality of education and student competencies. Society: A better organised student life can contribute to greater satisfaction, motivation, better health, and productivity in studies and work, which has a positive effect on society, higher GDP, and lower costs due to reduced absence from work, illness, etc. Originality: The research combines existing theoretical approaches with innovative solutions, such as digital tools for task organisation and AI, and emphasises the importance of long-term implementation of techniques. Limitations / further research: The small sample size and subjectivity of the results represent limitations. Further research with a larger sample and long-term follow-up is suggested.